Case for diagnosis. Linear Darier's disease - Fernanda Del Pintor Bidoia; Bruna Martini Massanares; Eduardo Vinicius Mendes Roncada; Luiza Vasconcelos Schaefer (Sociedade Brasileira de Dermatologia, 2018)
Abstract: We present a different and rare manifestation of Darier's disease, namely linear Darier's disease. Only a few cases have been described in the literature. The case report is a male patient, 60 years old, presenting brown to red papules and plaques with hyperkeratosis distributed on the abdomen, following Blaschko's lines, with 6 years' evolution. It was a difficult diagnosis until the dermatological workup and biopsy.